2015
DOI: 10.1186/s12909-015-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition and retention of ECG interpretation skills after a standardized web-based ECG tutorial–a randomised study

Abstract: BackgroundElectrocardiogram (ECG) interpretation is of great importance for patient management. However, medical students frequently lack proficiency in ECG interpretation and rate their ECG training as inadequate.Our aim was to examine the effect of a standalone web-based ECG tutorial and to assess the retention of skills using multiple follow-up intervals.Methods203 medical students were included in the study. All participants completed a pre-test, an ECG tutorial, and a post-test. The participants were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 35 publications
1
58
1
Order By: Relevance
“…It remains important to review whether these novel teaching and learning methods are effective 26. Previous studies have shown that students’ knowledge of, and skills in the analysis and interpretation of ECGs improve with computer-assisted instruction (CAI) 27–34. However, these studies did not compare CAI to other methods of instruction and thus it cannot be concluded that CAI is better than traditional methods of ECG teaching.…”
Section: Introductionmentioning
confidence: 99%
“…It remains important to review whether these novel teaching and learning methods are effective 26. Previous studies have shown that students’ knowledge of, and skills in the analysis and interpretation of ECGs improve with computer-assisted instruction (CAI) 27–34. However, these studies did not compare CAI to other methods of instruction and thus it cannot be concluded that CAI is better than traditional methods of ECG teaching.…”
Section: Introductionmentioning
confidence: 99%
“…This study reports descriptive statistics from an online training course taken by a large group of self-selected multinational and multidisciplinary healthcare professionals and was not designed to be a randomised controlled trial. Retention of information was also not assessed, an important caveat given some evidence suggests ECG interpretation test scores reduce 2–4 weeks post-education 20. In addition, other factors that may have influenced individual performance, such as prior experience in ECG interpretation in athletes, other educational courses completed or how long participants took to complete a module, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has explored and compared various teaching techniques, including self-directed learning (eg, online courses or modules), lecture-based or workshop-based formats and small-group peer teaching 4 5. Although no single method has emerged as superior, it is clear that newly acquired ECG interpretation skills must be continually reinforced for content retention 6–8. Thus, medical educators are not only challenged to deliver effective teaching methods, but they are also tasked with finding an educational approach that will help ensure enduring, sustainable progress.…”
Section: Teaching Electrocardiography Is Not Easymentioning
confidence: 99%
“…Ideally, ECG interpretation training methods should be efficient, flexible, sustainable, and capable of taking learners from a novice to an advanced interpreter level. In the modern era of technology-based medical education, online training or ‘e-learning’ has emerged as a promising and increasingly popular educational format 6. Online self-directed learning methods are often referred to as a ‘flipped-classroom’ approach, in which online modules are completed on the learner’s own time and then later reinforced through clinical application.…”
Section: Teaching Electrocardiography Is Not Easymentioning
confidence: 99%